Risk factors in oil and gas industry returns: International evidence - Ramos, Sofia B. (2014)
The recent boom in oil prices has attracted many investors to oil companies in search of both returns and diversification benefits. This analysis of the risk factors of investing in the oil and gas industry in 34 countries finds evidence that oil price is a globally priced factor for the oil industry. The oil and gas sector in developed countries responds more strongly to oil price changes than in emerging markets. Oil and gas industry returns also respond asymmetrically to changes in oil prices; oil price rises have a greater impact than oil price drops. There is no parallel to the asymmetry of oil price changes in other industries related to commodities. If there is any asymmetry, it is in the opposite direction from oil. Negative commodity price changes have a greater impact than positive ones. The results seem to indicate that the oil and gas industry is distinguished by a pass-through effect.